PROBATION WORK DEVELOPMENT DIRECTIONS IN THE LIGHT OF THE EUROPEAN PROBATION RULES - Barbara Stańdo-Kawecka (Probacja)
This article focuses on the European Probation Rules of 2010. It shows their genesis, the objectives taken into account in the course of work on them and the basic principles of probation activities formulated in them. Much attention was paid to terminological problems resulting from the diversity of agencies dealing with probation work in individual European countries. Probation work according to the European Probation Rules is essentially related to the implementation of community sanctions and measures imposed on adult suspects and convicted persons. The tasks of probation officers for family cases in Poland do not fall within the scope of probation activities understood in this way. The European Probation Rules cannot be ignored in works on the strategy for development of the probation service in Poland. However, the differences in the tasks and working methods of probation officers for adult offenders and for family cases should also be taken into account.